A Photonic Approach for Doppler Frequency Shift Measurement With Dispersion Medium - Chongyin Yi; Hao Chi; Tao Jin (IEEE Photonics Journal)
We propose and experimentally demonstrate a novel and simple approach to identifying both the direction and value of Doppler frequency shift (DFS) in this paper. A pair of phase modulators, as well as a dispersion medium in between them, are employed in the approach. The different dispersion-induced phase shifts of the upper and lower sidebands after passing the dispersion medium can be used to determine the direction of DFS. The value of DFS is characterized by measuring the frequency of the output signal from a low-speed photodetector. Experimental results verify the feasibility of the approach. The major advantages of the approach lie in that it can measure both the DFS direction and value while avoids the use of complicated modulators and additional reference signal, which greatly simplifies the system's architecture.